Income tax: A comparison of the forecasting methodologies - Pavlik, Martin (Podatek dochodowy: porównanie metod prognozowania, 2013)
The author focuses on income tax forecasting. He compares the different forecasting methodologies. He also compares his solution to the official annual forecasts in the Slovak Republic. He chose the quarters of years as the time units.
Ekonometria = Econometrics, 2013, Nr 3 (41), s. 104-112
Keywords: income tax; forecasting; ARCH models; GARCH models; EGARCH models; Akaike information criteria; podatek dochodowy; prognozowanie; kryterium informacyjne Akaikego